Safety of Intradermal/Subcutaneous Lidocaine With Epinephrine Use in Dermatologic Surgery. Issue 1 (January 2020) - Hirshburg, Jason M.; Diven, Dayna G.; Edmiston, Chloe; Dozier, Susan E.; Woody, Meghan; Fox, Matthew C.
Abstract : BACKGROUND: Recently, the safety of lidocaine plus epinephrine use in outpatient surgery has come under scrutiny despite its long history of use in outpatient dermatologic procedures and surgeries. OBJECTIVE: To assess the frequency of crash cart and other emergency interventions during Mohs micrographic surgery when lidocaine plus epinephrine is used as a local anesthetic and evaluate patient comorbidities associated with these events. MATERIALS AND METHODS: A retrospective chart review was conducted in an outpatient Mohs micrographic surgery clinic. RESULTS: One thousand one hundred twenty-seven Mohs cases were reviewed from the period of March 2015 to June 2016 with 864 meeting the inclusion criteria of patient weight, medical history, and amount of lidocaine administered recorded. No adverse events requiring emergency intervention with a crash cart or transfer to the emergency department occurred despite a patient population with advanced age and a wide range of comorbidities. CONCLUSION: No serious adverse events requiring emergency intervention were associated with lidocaine with epinephrine doses administered below the Food and Drug Administration recommended maximum. The authors did not find evidence from this study or after a literature search to support the requirement for a crash cart and other emergency equipment to be present during procedures.